2021
DOI: 10.1371/journal.pone.0257057
|View full text |Cite
|
Sign up to set email alerts
|

Indirect markers for length adjustment in distal biceps tendon allograft reconstruction

Abstract: Chronic musculotendinous retraction, shortening and fibrosis after distal biceps tendon tears makes a primary reconstruction often difficult or even impossible. Interposition reconstruction with allograft provides a solution, however there is no consensus about appropriate intraoperative graft length adjustment. Therefore, the purpose of this study was to find a practical reference value for distal biceps tendon length adjustment. Three-dimensional surface models of healthy distal biceps tendons were created b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
1
0
1
Order By: Relevance
“…Finally, prior anatomic studies have shown that the tendon ranges from 6.3 to 9.2 cm in length to 2.9 to 6 mm in diameter, 8 , 9 whereas Beeler et al. 10 found that various radiographic measurements can reliably predict native tendon length. As such, final reconstruction should aim to approximate the native tendon while maintaining an appreciation for the existing length-tension relationship.…”
Section: Discussionmentioning
confidence: 97%
“…Finally, prior anatomic studies have shown that the tendon ranges from 6.3 to 9.2 cm in length to 2.9 to 6 mm in diameter, 8 , 9 whereas Beeler et al. 10 found that various radiographic measurements can reliably predict native tendon length. As such, final reconstruction should aim to approximate the native tendon while maintaining an appreciation for the existing length-tension relationship.…”
Section: Discussionmentioning
confidence: 97%
“…Анатомические и МРТ-исследования показывают расширение нативного ДСДМП области лучевой бугристости от ±5,3 мм до ±19,4 мм сухожильно-мышечного перехода со средней длиной сухожилия 69 мм. Зона прикрепления к кости сухожилия имеет вариабельные параметры длины 14-21 мм и ширины (2-10 мм), а также С-образную конфигурацию [3,23,24]. В момент перемещения предплечья из положения супинации в положение пронации происходит сужение на ПРУП ≤45%, что приводит к механическому импиджменту ДСДМП без статического и динамического усилия окружающих мышц, являясь первичной причиной разрыва единичных сухожильных волокон.…”
Section: Discussionunclassified